Nutrient uptake by leaf - Murillo Castillo, Ritma Giordana (2013)
Foliar fertilization is an effective practice to correct nutritional deficiencies in plants that are under stress conditions or in soils with low nutrient availability, and consists in applying nutrient solutions directly on leaves. Nutrient absorption in the leaf occurs mainly through the epidermis, by diffusion, due to the nutrient concentration gradient established between the leaf surface and the epidermis interior. Once the nutrient has entered the cytoplasm of the epidermal cells, its movement happens in a relatively expedited fashion. The main barrier the nutrient has to pass is the cuticle, which is comprised of waxes. The physico-chemical characteristics of the nutrient, such as size and polarity, control the absorption rate. The present article provides a detailed description of the foliar absorption of nutrients and its influence on the development and use of foliar fertilizers.